ACR Appropriateness criteria® for nasopharyngeal carcinoma. Issue 7 (30th April 2016) - Saba, Nabil F.; Salama, Joseph K.; Beitler, Jonathan J.; Busse, Paul M.; Cooper, Jay S.; Jones, Christopher U.; Koyfman, Shlomo; Quon, Harry; Ridge, John A.; Siddiqui, Farzan; Worden, Francis; Yao, Min; et al.
Abstract: Background: Nasopharyngeal carcinoma (NPC) presents mostly with locally advanced disease and is treated with multimodal therapy; however, consensus is lacking for different clinical scenarios. Methods: The American College of Radiology (ACR) Appropriateness Criteria® are evidence‐based guidelines for specific clinical conditions that are reviewed every 3 years by a multidisciplinary expert panel. The guideline development and review include an extensive analysis of current medical literature from peer‐reviewed journals and the application of a well‐established consensus methodology (modified Delphi) to rate the appropriateness of imaging and treatment procedures by the panel. In those instances in which evidence is lacking or not definitive, expert opinion may be used to recommend imaging or treatment. Results: The ACR Expert Panel on Radiation Oncology – Head and Neck Cancer developed consensus recommendations for guiding management of nasopharyngeal carcinoma. Conclusion: Multidisciplinary evaluation is essential to guiding the optimal use of surgery, radiation, and systemic therapy in this disease. © 2015 Wiley Periodicals, Inc. Head Neck 38: 979–986, 2016